Critical Analysis of the Salafi Group’s Concept of Religious Thought - Muh Ade Saputra; Indo Santalia (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This paper aims to elaborate the main tenets of Salafi thought in religious practice and to present rebuttals put forward by Islamic scholars and thinkers. Through this approach, readers are expected to gain a more objective understanding of the dynamics of Salafi thought, thereby contributing to more harmonious religious dialogue within the pluralistic society of Indonesia. This paper is based on a literature review of primary sources, such as Salafi texts and the works of critical scholars, as well as a comparative analysis to minimize bias. The findings indicate that the core elements of Salafi thought include the emphasis on pure taw??d, the rejection of bid?ah (religious innovations), and strict adherence to the Sunnah, all of which aim to purify Islam. However, rebuttals from Ahl al-Sunnah scholars argue that this approach is overly extreme and has the potential to cause division. The conclusion drawn from social and political critiques of Salafi thought is that, although this movement is committed to purifying religious practices and returning to the teachings of the early generations (al-salaf al-??li?), it often faces serious challenges and criticism in the social and political spheres. Overall, the main criticism is that Salafi efforts at religious purification frequently generate socio-political problems due to their rigid and anti-pluralistic approach, as well as their complex and sometimes contradictory stance toward authority and involvement in practical politics.